PENGARUH INFLASI DAN EKSPOR MINYAK KELAPA SAWIT TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA MENGGUNAKAN MODEL DINAMIS REGRESSION - Isfihani Isfihani; Devi Andriyani (LPPM Universitas Malikussaleh – Indonesia, 2019)
This study aims to determine the effect of inflation and export of palm oil on the economic growth in Indonesia in the short and long term. The data used is the time series data from 1988 to 2016. The data analysis method used is the Auto Regressive Distributed Lagged (ARDL) approach and the analysis tool with the help of Eviews 9. The results of the study show that all stationary variables at the level of first difference and have long-term cointegration. Partially, in the short term analysis shows that inflation has a negative and significant effect on the economic growth, and exports of palm oil have a positive and insignificant effect on the value of economic growth in Indonesia. In the long-term analysis of inflation and export of palm oil has a negative and significant effect on the economic growth in Indonesia. The results of the stability model test show that the model used is stable. The result of the determination coefficient R 2 is 87.40 percent